Symposium 9: Professional Communities – Potentials and Limits of Blended Learning Scenarios - Logar, Sylvia; Schrittesser, Ilse; Wenninger, Barbara (Proceedings of the International Conference on Networked Learning, 2006)
The following paper deals with the development of professionalised action in the context of teacher education and training on the basis of a new group formation that we call ‘Professional Community’. This involves the implementation of heterogeneous groups as face-to-face as well as virtual structures with the mission to generate profession related knowledge and skills on a meta-level of communication and interaction. The concept of the ‘Professional Community’ is supported by an extended empirical study, which puts the theoretical framework into a concrete context, with the purpose of testing its assumed potential.